2016
DOI: 10.1039/c6cc02374f
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept for inhibiting metastasis: circulating tumor cell-triggered localized release of anticancer agent via a structure-switching aptamer

Abstract: Existing drug delivery systems were not suitable for killing cells in the circulatory system specifically. Herein, we developed a novel localized drug delivery strategy, in which the release of anticancer agents was specifically triggered by circulating tumor cells. Meanwhile, damage to non-target cells was avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It suggested that there is no loss happened during the assembly of four ssDNA, thus the concentration of DNA‐tetra was equal to the concentration of ssDNA. As shown in Figure 1B, the electrophoretic band of DNA‐1 containing one DNA aptamer sequence [ 23 ] was below 200 bp, and that of DNA‐3 containing three DNA aptamer sequences was above 200 bp. All the three DNA‐tetras ran slowly comparing with P2 (ssDNA, 106 bp), verifying the formation of DNA‐tetras.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that there is no loss happened during the assembly of four ssDNA, thus the concentration of DNA‐tetra was equal to the concentration of ssDNA. As shown in Figure 1B, the electrophoretic band of DNA‐1 containing one DNA aptamer sequence [ 23 ] was below 200 bp, and that of DNA‐3 containing three DNA aptamer sequences was above 200 bp. All the three DNA‐tetras ran slowly comparing with P2 (ssDNA, 106 bp), verifying the formation of DNA‐tetras.…”
Section: Resultsmentioning
confidence: 99%
“…A versatile approach to aptamer immobilization involves the modification of SA or its analogues (avidin, neutravidin) on the surface and then further reacting with biotin-terminated aptamers. Initially, SA was physically adsorbed on the clean surface of a glass or PDMS substrate, , but with poor stability and controllability. Subsequently, covalent modification of SA was developed and attracted more research interest.…”
Section: Interface Functionalization Of Aptamersmentioning
confidence: 99%
“…In light of the crucial roles of CTCs in metastasis, capturing and inhibiting CTCs would prevent metastasis. Wang’s group proposed CTC-triggered localized drug release strategies using structure-switching aptamers. , For example, they designed aptamer-functionalized DNA tetrahedrons containing chemotherapy drugs (doxorubicin, Dox) and a photosensitizer . As shown in Figure D, in the “sense” microchannel, the conformational change of aptamers upon the recognition of CTCs led to the release of DNA nanostructures, which subsequently flowed into “treat” microchannel.…”
Section: Aptamer-based Isolation Release and Analysis Of Ctcsmentioning
confidence: 99%